1999
DOI: 10.1021/ja982085y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bimodal Coordination Structure in Nitrosyl Heme Complexes through Hyperfine Couplings with Pyrrole and Protein Nitrogens

Abstract: Orientation-selected three-pulse ESEEM experiments have been performed on a series of nitrosyl hemoproteins:  HbNO in its two quaternary (R/T) states, the isolated NO-ligated α(β)-chains of hemoglobin, two hybrids of hemoglobin with asymmetrically ligated α(β)-chains, NO−myoglobin, and NO−Fe2+(TPP)−imidazole model complexes. The ESEEM spectra of the native complexes clearly revealed the contribution from two conformational states of the NO−heme group. At 4.2 K the αNO and βNO chains were found in an almost pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 50 publications
(125 reference statements)
4
73
1
Order By: Relevance
“…The spectra were recorded directly after freezing the same amounts of the living cell cultures. The spectra are dominated by an orthorhombic EPR signal, which is typical for a six-coordinated Fe 2ϩ ⅐heme(NO) complex (22)(23)(24)(25)(26)(27)(28)(29)(30). Repeated experiments revealed that for the same quantity of cells, the EPR intensity was found to be a factor 4 -6 higher for the cell cultures overexpressing mutant Ngb than for those overexpressing wt Ngb (see Fig.…”
Section: Expression Cloning and Purification Of Recombinant Wild Typementioning
confidence: 94%
See 1 more Smart Citation
“…The spectra were recorded directly after freezing the same amounts of the living cell cultures. The spectra are dominated by an orthorhombic EPR signal, which is typical for a six-coordinated Fe 2ϩ ⅐heme(NO) complex (22)(23)(24)(25)(26)(27)(28)(29)(30). Repeated experiments revealed that for the same quantity of cells, the EPR intensity was found to be a factor 4 -6 higher for the cell cultures overexpressing mutant Ngb than for those overexpressing wt Ngb (see Fig.…”
Section: Expression Cloning and Purification Of Recombinant Wild Typementioning
confidence: 94%
“…Electron paramagnetic resonance (EPR) has been used for more than thirty years to analyze nitrosyl (NO) ligation to the heme group of different hemeproteins (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The NO radical bound to the central Fe 2ϩ ion in a hemeprotein forms a paramagnetic, low-spin (S ϭ 1 ⁄2) complex, which can be detected by EPR.…”
mentioning
confidence: 99%
“…where N is the nuclear Zeeman frequency, a N is isotropic hyperfine coupling constant, K is the quadrupole coupling constant, and is the asymmetry parameter (21).…”
Section: Analysis Of the Fate Of Pyruvate In The Presence Of Reduced mentioning
confidence: 99%
“…They correspond to ⌬I ϭ 2 nuclear transitions and are, to the first order, insensitive to orientation broadening. It is possible to obtain a rough estimate of the hyperfine coupling constant a (supposed to be mainly isotropic) and quadrupolar coupling constant K from the frequency position of the dqdq correlation peaks using equation 1 ( being the asymmetry parameter) (37). Thus, a nitrogen atom ligated to a Fe-S cluster is easily detectable due to the strong coupling of the nuclear spin (I ϭ 1) with the unpaired electron.…”
Section: An Exchangeable Site At the [4fe-4s] Cluster Of The Tmhydf Pmentioning
confidence: 99%